LITUANISTIC ACTIVITY AT THE UNIVERSITY OF TASMANIA - TAŠKŪNAS, VINCAS J. (Knygotyra, 2015)
In this survey Lituanistic activity at the University of Tasmania is presented and the accumulation of Lithuanian expatriates’ manuscripts and printed heritage is discussed.